2001
DOI: 10.1161/hc4301.097194
|View full text |Cite
|
Sign up to set email alerts
|

An Iron-Binding Exochelin Prevents Restenosis Due to Coronary Artery Balloon Injury in a Porcine Model

Abstract: Background-Vascular smooth muscle cell (VSMC) proliferation is a critical factor in the neointima formation that causes restenosis after coronary angioplasty (PTCA). Desferri-exochelin 772SM (D-EXO), a highly diffusible, lipophilic iron chelator secreted by Mycobacterium tuberculosis, inhibits proliferation of VSMCs in culture. We hypothesized that treatment with D-EXO would inhibit neointima formation in balloon-injured vessels in vivo. Methods and Results-We subjected 24 pigs to overstretch coronary artery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…While this cofactor is a bacterial product obtained from cloning of the protein in bacteria, surely a serendipitous finding, we suggest that mouse urine contains an equivalent factor. Hence Ngal is a siderophore delivery protein for the proximal tubule, and this study is one of the first to use a bacterial siderophore in vivo (62).…”
Section: Discussionmentioning
confidence: 99%
“…While this cofactor is a bacterial product obtained from cloning of the protein in bacteria, surely a serendipitous finding, we suggest that mouse urine contains an equivalent factor. Hence Ngal is a siderophore delivery protein for the proximal tubule, and this study is one of the first to use a bacterial siderophore in vivo (62).…”
Section: Discussionmentioning
confidence: 99%
“…A link between iron and the development of atherosclerosis has been the subject of debate for more than two decades. 4,26 Recent studies have shown that administration of an iron-chelating agent suppresses neointimal formation in the balloon-injured porcine artery 27 and that an iron-deficient diet blocks atherogenesis in atherosclerosisprone animal models. 5 These findings indicate that iron is involved in the generation of vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Both coronary artery sections are at the same magnification. Reprinted with permission from Rosenthal et al (52). To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars a common complication of balloon angioplasty.…”
Section: Restenosismentioning
confidence: 99%
“…To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars a common complication of balloon angioplasty. The potential usefulness of desferri-exochelins for prevention of restenosis that is associated with coronary artery angioplasty was tested in a pig model (52). Anesthetized pigs subjected to overstretch coronary artery injury with coronary angioplasty balloons develop stenosis within a month.…”
Section: Restenosismentioning
confidence: 99%
See 1 more Smart Citation